2018
DOI: 10.1093/ajh/hpx222
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension Control in Adults With CKD in China: Baseline Results From the Chinese Cohort Study of Chronic Kidney Disease (C-STRIDE)

Abstract: Hypertension control was suboptimal among hypertensive CKD patients in China, especially among those overweight or with obesity, albuminuria, lower eGFR, and diabetes. Patients with uncontrolled hypertension should undergo treatment regimen evaluation to select the appropriate dosage and type of antihypertensive medications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 32 publications
3
31
0
Order By: Relevance
“…Chronic kidney disease (CKD) has a rapidly rising worldwide prevalence (Bruck et al, ; Ku, Johansen, & McCulloch, ; Yan et al, ). Moreover, CKD patients are at particularly high risk of death due to comorbidities such as infection, hypertension, atherosclerosis, heart failure, and stroke (DeBoer et al, ; Xu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic kidney disease (CKD) has a rapidly rising worldwide prevalence (Bruck et al, ; Ku, Johansen, & McCulloch, ; Yan et al, ). Moreover, CKD patients are at particularly high risk of death due to comorbidities such as infection, hypertension, atherosclerosis, heart failure, and stroke (DeBoer et al, ; Xu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, most patients have difficulty reaching this target BP level. Prior research has repeatedly found a range of 50-75% for uncontrolled BP among patients [9][10][11]. The evidence suggests that uncontrolled BP was a major risk factor for cardiovascular morbidity and mortality in the CKD population, in addition to the development of end-stage renal disease (ESRD) [1].…”
Section: Introductionmentioning
confidence: 99%
“…As a developing country with a heavy CKD burden, the control rate for hypertension in CKD patients in China has been improved in recent years. In the C‐STRIDE study, approximately 60% of CKD patients had a BP < 140/90 mmHg, which was higher than in such patients in previous reports . However, this is still not optimal, particularly among the participants with CKD stages 3 and 4 when compared to other studies, including the Chronic Renal Insufficiency Cohort (CRIC) .…”
Section: Discussionmentioning
confidence: 78%
“…As reported in our previous study, a total of 3472 participants were enrolled until June 2016, of whom 2873 participants had a complete record of BP measurement and/or antihypertensive medication histories. The prevalence of hypertension was 78.4%, with 2251 hypertensive CKD subjects . Among the hypertensive participants, a subgroup of 2213 subjects who had complete information on antihypertensive medication at enrollment was further analyzed in the present study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation